FoxO1 signaling in B cell malignancies and its therapeutic targeting - Hlavac, Krystof; Pavelkova, Petra; Ondrisova, Laura; Mraz, Marek (FEBS letters, 2024)
FoxO transcription factors (FoxO1, FoxO3a, FoxO4, FoxO6) are a highly evolutionary conserved subfamily of the 'forkhead' box proteins. They have traditionally been considered tumor suppressors, but FoxO1 also exhibits oncogenic properties. The complex nature of FoxO1 is illustrated by its various roles in B cell development and differentiation, immunoglobulin gene rearrangement and cell-surface B cell receptor (BCR) structure, DNA damage control, cell cycle regulation, and germinal center reaction. FoxO1 is tightly regulated at a transcriptional (STAT3, HEB, EBF, FoxOs) and post-transcriptional level (Akt, AMPK, CDK2, GSK3, IKKs, JNK, MAPK/Erk, SGK1, miRNA). In B cell malignancies, recurrent FoxO1 activating mutations (S22/T24) and aberrant nuclear export and activity have been described, underscoring the potential of its therapeutic inhibition. Here, we review FoxO1's roles across B cell and myeloid malignancies, namely acute lymphoblastic leukemia (ALL), acute myeloid leukemia (AML), chronic lymphocytic leukemia (CLL), follicular lymphoma (FL), diffuse large B cell lymphoma (DLBCL), mantle cell lymphoma (MCL), Burkitt lymphoma (BL), Hodgkin lymphoma (HL), and multiple myeloma (MM). We also discuss preclinical evidence for FoxO1 targeting by currently available inhibitors (AS1708727, AS1842856, cpd10).
Keywords: B cell malignancies; cpd10; leukemia; AS1842856; B cell development; FoxO1 inhibitor; lymphoma; FoxO1; targeted therapy; chronic lymphocytic leukemia